2007
DOI: 10.4049/jimmunol.178.4.1975
|View full text |Cite
|
Sign up to set email alerts
|

Unique Human Tumor Antigens: Immunobiology and Use in Clinical Trials

Abstract: The individual, unique tumor Ags, which characterize each single tumor, were described 50 years ago in rodents but their molecular characterization was limited to few of them and obtained during the last 20 years. Here we summarize the evidence for the existence and the biological role of such Ags in human tumors, although such evidence was provided only during the last 10 years and by a limited number of studies, a fact leading to a misrepresentation of unique Ags in human tumor immunology. This was also due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 49 publications
3
91
0
1
Order By: Relevance
“…HLA-DR tetramers loaded with MAGE-A3 anchor-tailored analogues, however, were unable to bind and sort low-affinity CD4 1 T cells from the polyclonal T-cell line, which remained in the negatively sorted fraction. This observation is consistent with the poor efficiency of HLA-DR tetramers in binding T cells bearing low-affinity TCR [10,12], which include CD4 1 T-cell responses specific for peptides derived from non-mutated TAA, such as the cancer-testis family [50,51].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…HLA-DR tetramers loaded with MAGE-A3 anchor-tailored analogues, however, were unable to bind and sort low-affinity CD4 1 T cells from the polyclonal T-cell line, which remained in the negatively sorted fraction. This observation is consistent with the poor efficiency of HLA-DR tetramers in binding T cells bearing low-affinity TCR [10,12], which include CD4 1 T-cell responses specific for peptides derived from non-mutated TAA, such as the cancer-testis family [50,51].…”
Section: Discussionsupporting
confidence: 68%
“…HLA-DR tetramers loaded with MAGE-A3 anchor-tailored analogues, however, were unable to bind and sort low-affinity CD4 1 T cells from the polyclonal T-cell line, which remained in the negatively sorted fraction. This observation is consistent with the poor efficiency of HLA-DR tetramers in binding T cells bearing low-affinity TCR [10,12], which include CD4 1 T-cell responses specific for peptides derived from non-mutated TAA, such as the cancer-testis family [50,51].A possible drawback of using MHC class II tetramers loaded with anchor-tailored peptide analogues is that they can narrow the TCR clonal representation of the bound T cells. It has been shown that residues flanking the core peptide might be involved in the interaction between the TCR and the MHC class II-peptide complex [36,52].…”
supporting
confidence: 53%
“…Numerous studies indicate that the anti-tumor T-cell repertoire is directed toward multiple CTL epitopes derived from different antigens. 20,[34][35][36][37][38][39] Therapeutic exploitation of the complete potential of anti-tumor T cells can be achieved by adoptive transfer of expanded TILs or vaccination with autologous tumor cells (or lysates, HSPs, mRNA derived from the tumor). However, the cumbersome procedure to generate high numbers of autologous TILs, and often the failure to obtain tumor samples, severely hampers the application of these forms of non-defined personalized immunotherapy.…”
Section: Vaccination Strategies With Defined T-cell Epitope Containinmentioning
confidence: 99%
“…Lately, driven by these problems, different groups have made an argument in favor of personalized immunotherapy targeting the unique antigens caused by mutations 66 that are often only present in the tumor of one patient. 37,80,81 These tumor antigens are purely tumor specific, and therefore not tolerogenic, and are believed to be often crucial to the oncogenic process. 37,43 Furthermore, the natural immune response in some patients was found to be stronger against the unique antigens than the response against shared antigens.…”
Section: Selection Of Taa For T-cell Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation